Computer-Assisted Distraction Osteogenesis in the Treatment of Hemifacial Microsomia. Issue 6 (September 2016) - Yu, Hongbo; Wang, Bo; Wang, Minjiao; Wang, Xudong; Shen, Steve Guofang
Abstract : Purpose: To investigate the application of computer-assisted surgical planning and virtual guide in distraction osteogenesis for patients with hemifacial microsomia. Methods: Eight patients diagnosed with unilateral hemifacial microsomia were enrolled in this study. Preoperative surgical planning and simulation were performed on three-dimensional model. Distraction was simulated on virtual model and the new morphology of the mandible was predicted. Mandibular ramus osteotomy and distractor implant was performed under the guidance of tooth-borne virtual guide. Postoperative evaluation of the intervention was performed by comparison of surgical planning and actual result. Results: Preoperative planning, simulation, osteotomy and distractor implant under the guidance of virtual guide were performed successfully on all patients. Tooth-borne guide defined the osteotomy line and accurate position of distractor. Facial symmetry was greatly improved. The osteogenesis and neomandible contour was checked by postoperative computed tomography, and a good matching with the preoperative planning was achieved. Conclusions: Computer-assisted surgical planning and intraoperative virtual guide shows its great value in improving the accuracy of distraction osteogenesis and restoring facial symmetry. It is regarded as a valuable technique in this potentially complicated procedure.